Experimental investigation of PWHT and normalizing effects on SMAW low-carbon steel joint properties - Manik, Parlindungan; Firdhaus, Ahmad; Prasetya, Blinka Hernawan; Prayoga, Rhizky (SINERGI, 2026)
The influence of post-weld heat treatment (PWHT) followed by normalizing on the mechanical properties of AH36 low-carbon steel is significant, particularly in the context of marine applications, such as shipbuilding welded joints. According to the extant literature, PWHT has been demonstrated to reduce residual stresses and enhance microstructural uniformity. However, the suitable PWHT temperatures for AH36 steel welds to balance strength, ductility, and toughness prior to normalizing remain underexplored. The objective of this study is to ascertain the suitable PWHT temperatures prior to normalizing, with the aim of improving weld performance in marine environments. A parametric study was conducted on AH36 steel specimens welded using shielded metal arc welding. The specimens were subjected to PWHT at 0°C (as-welded), 450°C, 600°C, and 750°C, followed by normalizing. Tensile, bending, and Charpy impact tests were utilized to assess the mechanical properties against established maritime safety standards. The results show that 600°C is the optimal PWHT temperature, effectively reducing residual stresses and promoting microstructural homogeneity. This, in turn, ensures that welds meet safety standards while preserving mechanical integrity. Higher temperatures increased the risk of brittleness, while lower temperatures provided insufficient stress relief. This study demonstrates that precise selection of PWHT temperature prior to normalizing is critical for ensuring reliable welds in marine structures. It identifies the optimal condition that maximizes strength, ductility, and impact toughness of AH36 steel while satisfying the Indonesian Classification Bureau (BKI) maritime safety standards.